Flush valve issue causing delay of the plumbing works as well as tiling works for the bath rooms in BRACU NCP - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the flush valve issue that caused delay of the plumbing works as well as tiling works for the bath rooms in BRACU new campus project.